2004
DOI: 10.2131/jts.29.179
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimation of Myocardial Fibrosis Based on Receptor Occupancy for .BETA.2-ADRENERGIC Receptor Agonists in Rats

Abstract: To develop beta2-adrenergic receptor (AR) agonists with higher selectivity, it is essential to evaluate the cardiac side effects which are the most serious side effects of this class of drugs. We studied receptor occupancy of beta1-ARs in rats as a possible cause for the side effect of beta2-AR agonists, namely myocardial fibrosis. Myocardial fibrosis in rats was observed on Day 7 after the administration of salbutamol and terbutaline, both of which are selective beta2-AR agonists, at higher dose levels. To ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The less bound a drug is, the more efficiently it can traverse cell membranes or diffuse. A literature survey indicated that degree of protein binding for TBS varies between 4.3 and 29% depending on the method (Ryrfeldt and Ramsay 1984), type of protein (rat, bovine and human serum albumin (Ryrfeldt and Ramsay 1984;Tanaka et al 2004;Wang et al 2003) and drug concentration (Wang et al 2003). Furthermore, the estimated association constant (K = 4.11 9 10 4 L mol -1 ) and the number of the binding site (n = 1.06) for TBS on one molecule of bovine serum albumin can be taken as an indication of low protein binding (Wang et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The less bound a drug is, the more efficiently it can traverse cell membranes or diffuse. A literature survey indicated that degree of protein binding for TBS varies between 4.3 and 29% depending on the method (Ryrfeldt and Ramsay 1984), type of protein (rat, bovine and human serum albumin (Ryrfeldt and Ramsay 1984;Tanaka et al 2004;Wang et al 2003) and drug concentration (Wang et al 2003). Furthermore, the estimated association constant (K = 4.11 9 10 4 L mol -1 ) and the number of the binding site (n = 1.06) for TBS on one molecule of bovine serum albumin can be taken as an indication of low protein binding (Wang et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we chose to give a high dose of salbutamol to rats to evaluate β 2 -adrenoceptor agonist activity on the plasma levels of inflammatory cytokines and levels of stress-inducible proteins in various tissues. The dose of salbutamol of 60 mg/kg was chosen as a toxic dose, because this dose produces inflammation and myocardial fibrosis in rats at 7 days after intravenous administration (Tanaka et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Salbutamol was developed as a first β 2 -adrenoceptor selective agonist (Waldeck, 2002). The major toxic effects of salbutamol when rats are treated with high dose levels have been reported to be myocardial necrosis and fibrosis (Magnusson and Hansson, 1973;Libretto, 1994;Tanaka et al, 2004). High doses of salbutamol cause various biological alterations related to tissues expressing β 1 -and β 2 -adrenoceptors.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, augmented beta 2 ‐adrenergic receptor signalling may not only mediate leptin's effects on renal sodium reabsorption, but it may also facilitate the action of the adipokine to promote cardiac fibrosis . Additionally, although beta 2 ‐receptor stimulation causes lipolysis and suppresses the secretion of leptin in healthy adipose tissue, these adrenergic responses are attenuated in epicardial fat .…”
Section: The Interplay Of Obesity and Enhanced Leptin Receptor Signalmentioning
confidence: 99%
“…Intriguingly, beta 2 ‐adrenergic receptors may also be involved in systemic inflammation; their stimulation can enhance the synthesis of pro‐inflammatory cytokines . These effects may augment the actions of beta 2 ‐adrenergic receptor stimulation to cause cardiac fibrosis in the experimental setting …”
Section: The Interplay Of Obesity and Enhanced Leptin Receptor Signalmentioning
confidence: 99%